The Role of HRM in the Performance of Roti Gembong Gembul Bangkalan Madura Employees - Achmad Noval Mufai; Ilham Mukhamada; Adelia Eka Putri; Iriani Ismail (Formosa Journal of Applied Sciences, 2023)
The purpose of this research is to find out how human resource management affects employee performance at Roti Gembong Gembul Bangkalan Madura and how, from a business perspective, HRM at Roti Gembong Gembul Bangkalan Madura can improve performance results. Conducting interviews at the location of the research object is one of the techniques used and conducting library research. The purpose of this research finding is to find out how important human resource management is in improving employee performance and how to utilize HRM to do so.